The broad-spectrum antiviral functions of IFIT and IFITM proteins - Diamond, Michael S.; Farzan, Michael (Nature reviews. Immunology, 2013)
Key Points IFN-induced protein with tetratricopeptide repeats (IFIT) proteins — which are induced after type I interferon (IFN)- or IFN-regulatory factor 3 (IRF3)-dependent signalling — contribute to antiviral defence against some viruses by binding to components of the eukaryotic initiation factor 3 (eIF3) translation initiation complex and inhibiting protein translation. Mutant flaviviruses, poxviruses and coronaviruses lacking 2′- O methyltransferase enzymes are attenuated in wild-type primary cells and mice but pathogenic in the absence of IFIT1 expression. Thus, IFIT proteins restrict viruses lacking 2′- O methylation of the 5′ RNA cap. IFIT proteins form a multiprotein complex to bind viral RNA displaying a 5′-ppp motif. By sequestering viral RNA containing 5′-ppp, IFIT proteins function as both a pathogen sensor and an effector molecule. IFN-induced transmembrane protein (IFITM) proteins constitute a family of small IFN-inducible proteins. Unlike IFIT proteins, IFITM proteins have two transmembrane domains and block the replication of enveloped viruses, including influenza A virus, dengue virus, Ebola virus and SARS coronavirus, at a step before these viruses enter the cytosol. IFITM proteins seem to be specialized in their activity. IFITM3 makes the primary contribution to the control of influenza A virus in mice and probably humans, whereas other human and mouse IFITM proteins more efficiently restrict infection by Ebola virus and SARS coronavirus. The mechanisms by which IFITM proteins prevent the entry of enveloped viruses remain unclear, but they probably involve alterations in the properties or the trafficking of intracellular compartments where these viruses traverse cellular membranes. Recent interest in identifying interferon-stimulated genes that have activity against a wide range of viruses has advanced our understanding of the IFIT and IFITM families and shown the many mechanisms by which host factors can restrict viral replication. Over the past few years, several groups have identified new genes that are transcriptionally induced downstream of type I interferon (IFN) signalling and that inhibit infection by individual or multiple families of viruses. Among these IFN-stimulated genes with antiviral activity are two genetically and functionally distinct families — the IFN-induced protein with tetratricopeptide repeats (IFIT) family and the IFN-induced transmembrane protein (IFITM) family. This Review focuses on recent advances in identifying the unique mechanisms of action of IFIT and IFITM proteins, which explain their broad-spectrum activity against the replication, spread and pathogenesis of a range of human viruses.